An Efficient Technique for Double Faults Detection and their Locations Identification in Digital Microfluidic Biochip (International Journal of Automation and Smart Technology, 2025)
Progress of digital microfluidic biochip (DMFB) confronts for the defective and specious electrodes. Not only these hinder the routing of droplets but also the completion time of assay is influenced by those defective electrodes. As Microfluidic-based biochips are broadly used in the revolution of medical diagnosis, gigantic parallel DNA analysis, automatic drug discovery and real-time biomolecular recognition including numerous safety-critical applications, this biochip definitely responsible for appropriate and accurate result. Prior accepting it for perceptive purposes the microfluidic biochip must confirm its precision and robustness. In this article, an aspect of fast fault diagnosis appliance for perceiving double faults and recognizing the fault locations within the biochip is introduced. If the biochip is defect free then the proposed approach computes the traversal time as well. The suggested result outpoured that the propound technique is competent, efficacious as well as delineate signifying improvement over the surviving method. Furthermore this paper added expedient reconfiguration contrivance.